(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
Social networks have exploded in recent years, about a billion people are embedded in this environment. E-commerce has also spread rapidly over the past decade. A highly profitable and strategic field was perceived in social networks, therefore, so was the need to unite e-commerce with this information-rich environment. This work will address the concepts of this aspect of e-commerce, its formation, and the formats found in the network. It will address the types of actions carried out in the field of e-commerce based on the interaction between people, as well as examples found on the Internet.